Analytical model to predict dilation behavior of FRP confined circular concrete columns subjected to axial compressive loading - Shayanfar, Javad (2020)
Experimental research and real-case applications are demonstrating that the use of fiber–reinforced polymer (FRP) composite materials can be a solution to substantially improve circular cross section concrete columns in terms of strength, ductility, and energy dissipation. The present study is dedicated to developing a new model for estimating the dilation behavior of fully and partially FRP-based confined concrete columns under axial compressive loading. By considering experimental observations and results, a new relation between secant Poisson's ratio and axial strain is proposed. In order for the model to be applicable to partial confinement configurations, a confinement stiffness index is proposed based on the concept of confinement efficiency factor. A new methodology is also developed to predict the ultimate condition of partially FRP confined concrete taking into account the possibility of concrete crushing and FRP rupture failure modes. By comparing the results from experimental tests available in the literature with those determined with the model, the reliability and the good predictive performance of the developed model are demonstrated.